CONTEMPORARY ISLAMIC EDUCATION: - Endah Kusuma Dewi; Santoso Santoso; Kasinyo Harto; Mardiah Astuti (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
This research begins with the problem of the historical background, challenges, and strategies for increasing reform efforts in contemporary Islamic education, with the aim of research to extrapolate the historical background, challenges, and strategies for increasing reform efforts in contemporary Islamic education. While this research can provide theoretical contributions and practical contributions. Where the theoretical contribution can be used as a new paradigm for subsequent researchers to conduct studies on Contemporary Islamic Education: Historical Background, Challenges, and Strategies for Increasing Reform Efforts is very relevant and representative to be realised today, where this discipline is always up-to-date, actual, developing and updating in every era and generation. Furthermore, this research is a library research by examining various literatures related to